Correlates of children's compliance with moderate‐to‐vigorous physical activity recommendations: a multilevel analysis. (14th March 2016) - Pereira, S.; Borges, A.; Gomes, T. N.; Santos, D.; Souza, M.; dos Santos, F. K.; Chaves, R. N.; Barreira, T. V.; Hedeker, D.; Katzmarzyk, P. T.; Maia, J. A. R.
Abstract : This study aimed to investigate the association between individual and school characteristics associated with the number of school days children comply with moderate‐to‐vigorous physical activity (MVPA) recommendations. Sample comprises 612 Portuguese children, aged 9–11 years, from 23 schools. Time spent in MVPA was measured by accelerometry, while individual‐level correlates were obtained by anthropometry and questionnaires. School‐level variables were collected by questionnaire, and accelerometer wear time and season were also considered. Maximum likelihood estimates of model parameters were obtained via a multilevel analysis with children as level‐1, and school as level‐2. Children who spent more time in sedentary activities and girls were less likely to comply with MVPA/daily. More mature children and those who use active transportation to school were more likely to attain the PA recommendation. Furthermore, greater accelerometer wear time and spring season increased the chance to achieve the recommended MVPA. In terms of school‐level correlates, a greater number of available facilities was negatively associated with children MVPA compliance. Given the set of variables, our results showed that individual characteristics seem to be more relevant for children's compliance rates with PA/day than school context variables, which should be taken into account in the implementation of school policies and practices.